Endoscopic Endonasal and Transmaxillary Approach for Resection of Juvenile Nasopharyngeal Angiofibroma With Preoperative Embolization in a Child. Issue 5 (July 2021) - Bandoh, Nobuyuki; Katada, Akihiro; Kono, Michihisa
Abstract : Abstract: A 13-year-old Japanese boy with a 6-month history of bilateral nasal obstruction and a 3-week history of recurrent epistaxis from the right nose was admitted to our department. Nasal endoscopy revealed a reddish, smooth-walled tumor occupying the right nasal cavity. Computed tomography scan revealed a 3.5 × 4.5 × 7.0-cm heterogeneously enhancing mass involving the right nasal cavity and extending posteriorly to the nasopharynx, and laterally to the pterygopalatine fossa and the medial part of the infratemporal fossa. We diagnosed as juvenile nasopharyngeal angiofibroma with Radkowski classification stage IIC. The internal maxillary and ascending pharyngeal arteries were embolized with polyvinyl alcohol followed by Embosphere using a conventional Seldinger technique. En bloc resection was performed with an endoscopic ipsilateral endonasal and sublabial Caldwell–Luc transmaxillary approach under general anesthesia. As of 3 years postoperatively, no recurrence has been found. We report a child case of juvenile nasopharyngeal angiofibroma successfully treated with less invasive surgery with preoperative embolization.